2022
DOI: 10.1186/s12991-022-00383-5
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant salience relationship with first rank symptoms

Abstract: Background Aberrant salience is the incorrect assignment of salience, significance, or value to different innocuous stimuli that might precede the onset of psychotic symptoms. The present study aimed to perform a preliminary evaluation of potentially different correlations between the Aberrant Salience Inventory (ASI) score and dimensional or categorical diagnostic approaches. Methods 168 adult outpatients with a current psychiatric diagnosis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…However, even if part of our expectations were met (Psychosis [+] scored higher than the other two in most of the domains, and so did the Psychosis [-] when compared to the Neurologic controls), several of our hypotheses were not veri ed. ASI scores were quite similar between the Psychosis [+], Psychosis [-] and Neurologic cohorts; while the similarity between the two latter groups was rather predictable, we would expect the mean ASI score to be higher in adult patients with psychotic symptoms (Ballerini et al, 2022). This could be attributable to several different causes; rst of all, it could be an artifact of the yet small sample size.…”
Section: Discussionmentioning
confidence: 92%
“…However, even if part of our expectations were met (Psychosis [+] scored higher than the other two in most of the domains, and so did the Psychosis [-] when compared to the Neurologic controls), several of our hypotheses were not veri ed. ASI scores were quite similar between the Psychosis [+], Psychosis [-] and Neurologic cohorts; while the similarity between the two latter groups was rather predictable, we would expect the mean ASI score to be higher in adult patients with psychotic symptoms (Ballerini et al, 2022). This could be attributable to several different causes; rst of all, it could be an artifact of the yet small sample size.…”
Section: Discussionmentioning
confidence: 92%
“…To explain this aberrant salience perception, meaning is then ascribed to the stimulus, resulting e.g., in delusional thinking. There is extensive literature on aberrant salience processing in SZ and psychosis (Menon et al, 2005;Heinz and Schlagenhauf, 2010;Ballerini et al, 2022). To our knowledge however, there is only one study that found a positive association between the false perception of positive and neutral facial expressions and aberrant salience in patients with acute psychosis (Comparelli et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
“…For what concerns the psychotic group, this decision was made on the basis that impaired insight into illness, which is known to affect anxiety levels, is particularly severe during the first episodes of psychosis (Gerretsen, Plitman, et al, 2014), and to avoid confounding factors such as the impact of chronicity and/or dampened salience (Kapur et al, 2005) on the relationship between AS, PLEs and anxiety. Since AS appears to be a transdiagnostic feature of vulnerability to psychosis (Ballerini et al, 2022), in the psychotic sample no distinction was made regarding affective and non‐affective psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…While PLEs can be described as state-like transitory subclinical psychotic episodes (Fonseca Pedrero & Debbané, 2017), AS appears to be a transdiagnostic trait-like feature of general vulnerability to psychosis which usually remains stable over time (Li et al, 2020). However, increased scores on the "Aberrant Salience Inventory" (ASI) (Cicero et al, 2010), a useful tool to measure AS, tend to lead to more frequent and intense PLEs (Fonseca Pedrero & Debbané, 2017) and psychotic symptoms, but they did not differ in patients with any specific psychiatric diagnosis (Ballerini et al, 2022), thus confirming the transdiagnostic validity of AS. From our perspective, not only psychosis but also anxiety may represent one of the forms the vulnerability expressed by AS may take when confronted with particular experiences.…”
mentioning
confidence: 99%